THE ROLE OF USER SATISFACTION IN MEDIATING THE EFFECT OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON REUSE INTENTION (STUDY OF TIKET.COM USERS IN DENPASAR CITY) - Paramananda, Komang Agus Sathya; Sukaatmadja, I Putu Gde (International Journal of Social Service and Research, 2024)
The purpose of this study is to determine the influence of perception of ease of use and perception of benefits on reuse intention through user satisfaction and determine the role of user satisfaction in mediating the relationship between perceived ease and perceived usefulness and reuse intention. The research was conducted in the city of Denpasar, aimed at e-commerce users Tiket.co. The results of the t-test show that perceived ease of usage has a positive and significant effect on the reuse intention and user satisfaction of the platform users. In addition, user satisfaction is able to mediate this relationship, and is a mediator in this process.